Key Component related parameters. - Yihan Liu (2258221) (2025)
Harmonious High-Power AC Electric Locomotive, as the main type of locomotive for freight transport in China, the safety of its operation and maintenance issues have been the focus of great attention by the operation department. How to reduce the high maintenance cost and shorten the time-consuming long maintenance is a pressing issue for the operation management. In this paper, for the C4 repair operation of the harmonious electric locomotive, using the preventive maintenance method, we constructed a multi-component maintenance plan optimization model with the aim of maximizing the availability, and solved it by using a heuristic genetic algorithm. On this basis, component-specific maintenance schedules were developed based on reliability thresholds. The results of the study showed that the preventive maintenance approach resulted in a 51.04% reduction in total cost and a 7.89% increase in availability over the same operating cycle compared to the traditional fixed repair schedule maintenance program. Under the premise of ensuring locomotive operational safety, it effectively saves costs, reduces maintenance downtime and achieves the objective of improving the quality of C4 repairs.